The Evolution and Application of Design in Visual Communication and its Influence in Social Behavior - Carlos Antonio Valverde Lojano, (Technium Social Sciences Journal, 2020)
Today with the evolution of technology, interactive processes and transmedia narratives, social behavior in communication is changing. It is growing rapidly and influencing consumers of content and for audiences, the main objective is to study how communication is becoming increasingly iconic to the point that feelings begin to be plotted, such is the case of emoticons or emojis in short messages. For this purpose, a methodology based on scientific and bibliographical research on communicative language types and individual behavior is used, coupled with an exploratory field analysis based on user experiences on mobile devices. These results of the research will strengthen the study of trans-disciplinary contents that focus specifically on the application and generation of creative ideas in the field of production, interaction or realization of a communicative or interactive product. That using technology as a support and platform, the communicator or creator of communicative products creates needs in the users. Something very different happens in creativity, this is emotional, an awareness of what is wanted to be informed and how can it be informed, ¿what is its functionality? how do we want to reach the consumer this kind of creativity comes through the evolution of experiences.